Base editors for simultaneous introduction of C-to-T and A-to-G mutations - Sakata, Rina C; Ishiguro, Soh; Mori, Hideto; Tanaka, Mamoru; Tatsuno, Kenji; Ueda, Hiroki; Yamamoto, Shogo; Seki, Motoaki; Masuyama, Nanami; Nishida, Keiji; Nishimasu, Hiroshi; Arakawa, Kazuharu; et al. (Nature biotechnology, 2020)
We describe base editors that combine both cytosine and adenine base-editing functions. A codon-optimized fusion of the cytosine deaminase PmCDA1, the adenosine deaminase TadA and a Cas9 nickase (Target-ACEmax) showed a high median simultaneous C-to-T and A-to-G editing activity at 47 genomic targets. On-target as well as DNA and RNA off-target activities of Target-ACEmax were similar to those of existing single-function base editors.